Recurrence and Prognostic Value of Circulating Tumor Cells in Resectable Pancreatic Head Cancer: A Single Center Retrospective Study - Zhang, Qiao; Xia, Feng; Sun, Qiang; Cao, Wenjing; Mo, Ali; He, Weiming; Chen, Jiazhen; Zhang, Weiqiao; Chen, Weiqiang (Frontiers in Surgery, 2022)
Background and Aim To investigate the effect of preoperative circulation tumor cells (CTCs) on postoperative recurrence and overall survival prognosis of pancreatic head cancer after pancreaticoduodenectomy (PD). Methods From March 2014 to January 2018, 73 patients with pancreatic head cancer underwent radical resection (R0) in Zhongshan People's Hospital. CTCs in peripheral blood of patients with pancreatic head cancer were detected by “Cyttel” method before PD. Seventy-three patients were divided into positive and negative groups according to the positive criteria. To explore the relationship between the clinical data of CTCs and disease-free survival (DFS) and overall survival (OS). Cox proportional hazards model was used to analyzing the risk factors affecting the postoperative recurrence and the survival prognosis of patients. Results 41 patients (56.2%) were in the CTC-positive group. Preoperative CTCs were correlated with tumor vascular invasion, CA199 level and postoperative liver metastasis (P < 0.05). Preoperative CTC-positive, lymph node metastasis, vascular invasion, and nerve invasion were independent risk factors for DFS (P < 0.05). Preoperative CTC-positive, tumor diameter > 2 cm and vascular invasion were independent risk factors for OS of patients (P < 0.05). Conclusion The detection of CTCs before PD is an important factor affecting the DFS and OS of pancreatic head cancer, which is significant in guiding clinical work.